2016
DOI: 10.1017/s1460396916000054
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapists’ and Diagnostic Radiographers’ participation in continuing professional development and knowledge of Regulatory Body Registration

Abstract: BackgroundIrish healthcare has seen radical reforms in recent years. Regulatory Body Registration was introduced to improve patient care and regulate professionals. Continuing Professional Development (CPD) is a requirement of registration. Professionals need to keep up-to-date with new techniques and technologies while maintaining their skills.PurposeThis research assessed the factors affecting CPD participation in Radiation Therapists and Diagnostic Radiographers and their knowledge and attitudes towards Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…What matters is that such development is characterized as a growing process of awareness and mastery of know-how at work. This is evidenced in different researches that point to reflective practice as an important element for professional development processes [26,27]. Therefore, in addition to promoting training and development events for specific activities, leaders should encourage a critical and reflective vision in their respective work teams with a deliberately planned direction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…What matters is that such development is characterized as a growing process of awareness and mastery of know-how at work. This is evidenced in different researches that point to reflective practice as an important element for professional development processes [26,27]. Therefore, in addition to promoting training and development events for specific activities, leaders should encourage a critical and reflective vision in their respective work teams with a deliberately planned direction.…”
Section: Resultsmentioning
confidence: 99%
“…In this broader view of the professional development process, it stems from formal or informal learning actions [18], being directly related to career progression [11]. Thus, the concept of professional development encompasses a variety of practices, such as: activities in scientific societies [19]; training processes, including acting as supervisor, coach, or leader (mentoring and monitoring of actions to students, subordinates, or new professionals) [20]; training and strategies for systematized and informal learning for skills development [16,21,22]; in-service training [5,23]; participation in communities of practice [24,25]; participation in processes of continuous professional development [5,26]; peer collaboration mediated by technological resources [27,28]; mentoring programs [29]; and specific leadership development programs [10,30].…”
Section: Professional Developmentmentioning
confidence: 99%
“…CPD outcomes for radiographers and radiation therapists; including the motivational instigators and barriers linked with radiography CPD courses (Grehan et al, 2018), relevant aspects of CPD for radiographers (Marshall et al, 2008) and rationale affecting the radiographers and radiation therapists' participation in CPD courses (Walsh and Craig, 2016). While previous studies explored barriers affecting CPD courses, including IV cannulation (De Boo et al, 2020), the novelty of this study is that it investigates the association between an anatomy teaching and learning CPD course and the cannulation skills of the course participants.…”
Section: Research Studies Have Investigated Variousmentioning
confidence: 99%
“…The second group of papers reported that continuing professional development (CPD) was generally appreciated and valued [44][45][46][47]. CPD is now increasingly widespread and mandatory in the health and care professions [48].…”
Section: Education and Trainingmentioning
confidence: 99%